2016
DOI: 10.1007/s12088-016-0581-9
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic and Biocontrol Potential of Trichoderma asperellum ZJSX5003 Against the Maize Stalk Rot Pathogen Fusarium graminearum

Abstract: The efficacy of seven strains of Trichoderma asperellum collected from the fields in Southern China was assessed against Fusarium graminearum (FG) the causal agent of corn stalk rot of maize were in vitro for their antagonistic properties followed by statistical model of principal compound analysis to identify the beneficial antagonist T. asperellum strain. The key factors of antagonist activity were attributed to a total of 13 factors including cell wall degrading enzymes (chitnase, protease and b-glucanases)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 28 publications
1
68
0
2
Order By: Relevance
“…Application of Trichoderma strains on crops or crop residuals to inhibit the development and DON production of Fusarium is an available biological-based strategy. As potential BCAs, Trichoderma strains are capable of producing a large number of enzymes and secondary metabolites, which are effective components against pathogens and play an important role in the antagonistic action of Trichoderma [32]. Hydrolytic enzymes (such as chitinase and proteases) and antibiotics (such as polyketides and terpenes) derived from Trichoderma act as “weapons” against pathogens when in competition [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Application of Trichoderma strains on crops or crop residuals to inhibit the development and DON production of Fusarium is an available biological-based strategy. As potential BCAs, Trichoderma strains are capable of producing a large number of enzymes and secondary metabolites, which are effective components against pathogens and play an important role in the antagonistic action of Trichoderma [32]. Hydrolytic enzymes (such as chitinase and proteases) and antibiotics (such as polyketides and terpenes) derived from Trichoderma act as “weapons” against pathogens when in competition [32].…”
Section: Discussionmentioning
confidence: 99%
“…As potential BCAs, Trichoderma strains are capable of producing a large number of enzymes and secondary metabolites, which are effective components against pathogens and play an important role in the antagonistic action of Trichoderma [32]. Hydrolytic enzymes (such as chitinase and proteases) and antibiotics (such as polyketides and terpenes) derived from Trichoderma act as “weapons” against pathogens when in competition [32]. In addition, the potential UGTs inactivating DON in Trichoderma strains, act as “shields” to protect themselves against DON-producing pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responsible factors for the PGP ability of T. cerinum Gur1 appear to be secretion of phytohormone IAA, and enhanced availability of phosphorus and iron to plants by phosphate solubilization and siderophore production. As reported by several workers, increase in biomass is directly induced by production of plant growth promoting metabolites or through stimulation of nutrient uptake, and indirectly by production of lytic enzymes or antibiotics that protect plants from deleterious rhizosphere organisms (Hermosa et al 2012;Contreras-Cornejo et al 2016;Li et al 2016). …”
Section: In Vivo Studymentioning
confidence: 98%
“…Trichoderma spp. have been reported and accomplished in controlling fungal phytopathogens in various cases (Kubicek, 2001;Harman et al, 2004;Celar & Valic, 2005;Schwarze et al, 2012;Lee et al, 2012;Li et al, 2016). Although a lot of investigators have reported biocidal efficacy of Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%